Health Food Supplements (Health Food) Highly Nutritious From Chlorella And Oil Catfish (Pangasius hypopthalmus) - Syahrul Syahrul; Dewita Dewita (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
AbstractThe utilization of microalgae as a food ingredient considered effective, because in addition to alternative food sources also contains nutrients chlorella microalgae in particular is very good for health. This microalgae rich in protein (60.5%), fat (11%), carbohydrates (20.1%), water, dietary fiber, vitamins and minerals Besides these microalgae contain pigments (chlorophyll), tocopherol and the active component (antimicrobial and antioxidants). This is what underlies microalgae is very useful to be used as a source of raw materials of health food supplements. Currently the health food supplements have become a necessity for people to maintain their health in order to remain vibrant. This study aims to produce high nutritious health food supplements from raw material chlorella enriched with fish protein concentrate and oil catfish. The method used in the manufacture of high nutritious health food supplement is a method of microencapsulation with different formulations. The results showed that the best formulations based on the profile of amino acids, fatty acids and standards AAE per day especially essential fatty acids oleic and linoleic is formulation B (chlorella 2%, 1% fish oil and fish protein concentrate 1%.